Digitalisasi Administrasi Keuangan: Pendampingan Keuangan Rukun Tetangga Terintegrasi Di Tangerang Selatan - Retno Fuji Oktaviani; Hakam Ali Niazi; Yesi Puspita Dewi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This Community Service Program aims to enhance the capacity of the Rukun Tetangga (RT) management in the Bintaro Gallery Residential Area to manage finances effectively, transparently, and accountably through the implementation of an integrated, digital-based RT financial system. Methodology/approach: The program was carried out through several stages, including preparation, socialization, training on both manual and digital recording methods, technical assistance, and evaluation of learning outcomes using pre- and post-tests. Results: The results show a significant improvement in participants’ understanding and skills in financial recording, accurate report preparation, and awareness of the importance of data security. The difference between the pre- and post-test scores indicates the training’s success in transferring knowledge and skills to the participants. Conclusions: Mentoring not only facilitated technical mastery but also addressed implementation challenges while fostering confidence and accountability among RT administrators in managing resident contributions more efficiently. Overall, this activity represents a strategic step toward the digital transformation of RT financial management into a more effective, transparent, and reliable system. Limitations: The main limitations of this program are the relatively short training duration, which limits the depth of some materials, and the fact that some participants are still not fully accustomed to using digital technology in financial management. Contributions: This program contributes by providing a training model that can be replicated in other neighbourhood associations, encouraging digital transformation in community-level financial governance, and fostering greater participation and trust from residents in their RT management.